Health status and self-perception of health among homeless people in Spain: a mixed-methods study - Bedmar, Miguel A.; Capitán-Moyano, Laura; Bennasar-Veny, Miquel; Moreno-Mulet, Cristina; Carrero-Planells, Alba; Yáñez, Aina M. (Frontiers in Public Health, 2024)
Homelessness is a phenomenon of social exclusion and poverty that has increased alarmingly during recent years. Homeless people (HP) experience violations of several basic human rights or needs that impact their well-being. Therefore, the aim of this research was to assess the health status and self-perceived health of HP and examining the impact of homelessness on their health. Methods: We used an explanatory sequential mixed-methods approach that integrated a quantitative cross-sectional study within critical social and ethno-sociological qualitative frameworks. Data were collected in